Gestão social nos territórios rurais : limites e possibilidades do agreste de Alagoas - Alcantara, Fernanda Viana de (2013)
The theme of territorial development has attracted interests of different areas of knowledge. In this sense, it becomes necessary to think about the approach of territorial development in Brazil, which became wider at the beginning of the XXI century. This particular thesis aims to perform reflections on the process of preparing and implementing territorial actions to promote a development in rural areas; in this regard the discussion about the experience of Brazilian planning is recognized, and it is also aimed to understand the challenge of construction of mediation processes which are able to guide and operationalize territorial policies; it also aims to forward the interests for discussion that evidences the problematic of social management. The research has an exploratory and investigative character, performing an approach that ponders the territorial development through an analysis, from survey and literature review on the theme, and the analysis of data obtained through fieldwork, such as interviews with the main social actors bound to entities and members of social movements that contribute in the process of territorial development, taking as a parameter the main instance: the Rural Territorial Collegiate. It is acknowledged that the participation of civil society in the elaboration of public policies is significantly important, providing the transcendence of apparent contradictions of interests and visions inherent to public and private domain, particularly when referring to rural environments, in which an increasing on density of commitments and responses is aimed. It is to respond to the challenge of territorial development, in the face to the difficulty in forming government capacity of multiple commitments on strategic interplay of the actors. It refers to the recognition of the importance of the participation and interaction of different social actors in the attempt of delineating ways to territorial development. Also regarding to the discussion of territorial development, this job is linked to the references of the discussion about the rural environment in Portugal, especially the discussion of governance, through contact with Portugal Local Development Associations, although it is considered the significant and notable differences regarding to the territorial dimension and the socio-economic and environmental issues between these two countries. As a result of the research, it is evidenced that the Rural Development Policy in Brazil is a process in construction that still goes through difficulties regarding to its supporting pillars among which is called attention to social management; the data and conducted analysis reveal that there was a process of change in the manner and consequences of action planning in rural environment, and also reveal that there is an advance regarding to the innovation in the instruments of participation and valuing of local forces, from the point of view of the togetherness of different representations that are heterogeneous. And therefore, they try to find the ways to reduce social disparities in rural environment, through management, but still in a fragile way.